Likuiditas, Efisiensi Aset, dan Ukuran Perusahaan sebagai Penentu Profitabilitas di Industri Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia (2022–2024) - Dewi Safirah; Ario Purdianto; Benny Dhevyanto (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
The purpose of this study is to examine how profitability in food and beverage firms listed on the Indonesia Stock Exchange between 2022 and 2024 is impacted by liquidity, asset efficiency, and company size. Multiple linear regression analysis and a quantitative associative technique are used in this work. Purposive sampling was used to choose the sample, yielding a total of 33 observations from 11 firms. Secondary data from yearly financial reports posted on the Indonesia Stock Exchange's official website were used. The findings indicate that, in part, asset efficiency has a positive and significant impact on profitability with a significance value of 0.037, liquidity has a positive and significant impact with a significance value of 0.043, and company size has a positive and significant impact with a significance value of 0.028. With a significance value of 0.006, liquidity, asset efficiency, and business size all significantly affect profitability at the same time. According to the coefficient of determination, the independent variables account for 46.4% of the variation in profitability, with other factors outside the model influencing the remaining 53.6%. These results imply that improving business profitability is mostly dependent on effective asset utilization, good liquidity management, and a suitable firm size.